Sustainable Pharmacy: Piloting a Session on Pharmaceuticals, Climate Change, and Sustainability within a U.S. Pharmacy Curriculum - Katherine Gruenberg; Dorie Apollonio; Conan MacDougall; Tina Brock (University of Minnesota Libraries Publishing, 2017)
Objective: To design and assess an innovative session for pharmacy students that addresses the role of pharmaceuticals with climate change and sustainability. Innovation: One hundred and sixteen third-year students at the University of California, San Francisco School of Pharmacy participated during their required Health Policy course. This 3-hour session included guided pre-course activities, an interactive lecture, a panel of healthcare professionals discussing complex decision-making and small group case-based learning. Curricular assessment was conducted through pre-/post-test measures of knowledge acquisition, student evaluations, and course projects. Critical Analysis: One hundred and two students (response rate 88%) completed the pre-test and 115 students (response rate 99%) completed the post-test assessment. We identified a significant increase in the proportion of correct answers on post-test questions addressing drug disposal legislation (75% pre-test vs 91% post-test, p=0.002) and the predicted effects of climate change on health (55% pre-test vs 90% post-test, p < 0.001). The session was also well received; average student evaluation scores were above 4 in all areas of course evaluation (where 5=ideal). In addition, 17% of student groups (relative to 0% in 2015) proposed a sustainability-related policy as their final coursework project. Next Steps: The development and implementation of this brief session resulted in knowledge gain and favorable student response. This project is feasible for other Schools of Pharmacy to adapt and implement. Conflict of Interest: None   Type: Note